SMART WORK, SMART LIFE: IMPACT OF REMOTE WORK ON WOMEN IN THE IT SECTOR (Lex localis - Journal of Local Self-Government, 2025)
The COVID-19 pandemic accelerated the institutionalization of remote and hybrid work, reshaping both organizational practices and policy debates. While scholarship has extensively documented the benefits and challenges of telework, limited evidence exists on its gendered impact within the Indian IT sector and the governance mechanisms that can address these challenges. This study examines how remote work influences women’s work–life balance, productivity, job satisfaction, and career progression, while situating the findings within the broader policy and governance frameworks.A survey of 110 female IT professionals in India was conducted and analyzed using descriptive statistics and regression models. Results reveal that hybrid work is the most preferred arrangement, balancing autonomy with visibility. Yet, barriers such as limited visibility (52.7%), extended working hours (39.1%), and domestic interruptions (31.8%) persist. Regression findings show that organizational support (β = 0.41, p < .01) and flexible scheduling (β = 0.36, p < .05) enhance job satisfaction, whereas heavy domestic workloads reduce productivity (β = –0.32, p < .05).The study extends boundary theory and the flexibility paradox to the Indian IT context, while also highlighting the role of governance and policy enablers. By aligning organizational practices with national gender equity policies, Digital India initiatives, and local-level support mechanisms such as community childcare and digital infrastructure, this research provides actionable insights for designing equitable hybrid work models.